Análise semiótica do conto Passeio Noturno, de Rubem Fonseca - Assunção, Rosalina Brites de; Neves, Maria Helena de Moura [UNESP] (My University, 2010)
This paper presents an analysis of the short story Passeio Noturno I, by Rubens Fonseca, from the gerative way of sense, oriented by Greimas´ postulations of generative semiotics. For the semiotics, discourse is conceived as a superposition of levels of diferent depth which are articulated according to a way which goes from the abstract to the concrete (BARROS, 2001). Following the notion of gerative way, the analysis of the short story is three folded: the level of fundamental structures, the level of the narrative structures and the level of the discursive structures. The subject matter that underlies the structure of the short story refers to a critique of the violence present in capitalist society in which "voices of culture" coexist with "voices of barbarie".

Este trabalho apresenta a análise do conto Passeio Noturno I, de Rubens Fonseca, a partir do percurso gerativo do sentido, orientado pelos postulados da semiótica greimasiana. Para a semiótica, o discurso apresenta-se “como uma superposição de níveis de profundidade diferente, que se articulam segundo um percurso que vai do abstrato ao mais concreto” (BARROS, 2001). Assim, de acordo com a noção de percurso gerativo a análise do conto desenvolveu-se em três etapas: o nível das estruturas fundamentais, o nível das estruturas narrativas e o nível das estruturas discursivas. A temática que subjaz à estrutura do conto é uma crítica à violência presente na sociedade capitalista onde convivem as “vozes da cultura” e as “vozes da barbárie”.
Keywords: semiotic analysis; gerative way; discourse; narrative; discourse subject; análise semiótica; percurso gerativo; discurso; narrativa; sujeito do discurso